2018
DOI: 10.1016/j.kint.2018.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Implementing core outcomes in kidney disease: report of the Standardized Outcomes in Nephrology (SONG) implementation workshop

Abstract: There are an estimated 14,000 randomized trials published in chronic kidney disease. The most frequently reported outcomes are biochemical endpoints, rather than clinical and patient-reported outcomes including cardiovascular disease, mortality, and quality of life. While many trials have focused on optimizing kidney health, the heterogeneity and uncertain relevance of outcomes reported across trials may limit their policy and practice impact. The international Standardized Outcomes in Nephrology (SONG) Initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
149
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(151 citation statements)
references
References 42 publications
1
149
0
1
Order By: Relevance
“…Compared to previous studies in haemodialysis patients, our haemodiafiltration cohort generally reported fewer dialysis symptoms and quicker post-treatment recovery times [5,31]. However, in keeping with recent reports, we found that fatigue was the most commonly reported symptom by our haemodialysis patients [32]. The next most commonly reported dialysis-associated symptom was one of feeling the cold.…”
Section: Discussionsupporting
confidence: 74%
“…Compared to previous studies in haemodialysis patients, our haemodiafiltration cohort generally reported fewer dialysis symptoms and quicker post-treatment recovery times [5,31]. However, in keeping with recent reports, we found that fatigue was the most commonly reported symptom by our haemodialysis patients [32]. The next most commonly reported dialysis-associated symptom was one of feeling the cold.…”
Section: Discussionsupporting
confidence: 74%
“…Mortality also has a differentiated weighting: lower for patients and higher for clinicians and managers. Despite these differences in assessment among the stakeholders, only recently has the need to include the patient's perspective in a routine and explicit way been emphasized [23][24][25][26]. PROMs are a priority for patients and other stakeholders, reflecting their preferences, and should be systematically considered in evaluation systems.…”
Section: Discussionmentioning
confidence: 99%
“…The broad applicability of this outcome to all access types, the absolute necessity of a functioning vascular access to provide adequate dialysis, and the detrimental consequences of a failing access make this outcome a meaningful and suitable core outcome. A definition and metric for vascular access function is currently in development and will be piloted and validated in an international, multicentre study to ensure it is a reliable and feasible outcome measure to be used in research and routine clinical practice without adding undue burden to researchers and health professionals to ensure global implementation 1, 145,181 . Consistent reporting of a validated, feasible, robust and meaningful outcome measure for vascular access function in research and ultimately in quality improvement projects will help to inform clinical practice and decision making in a meaningful way.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the contributions of 1,376 participants from 73 countries, the four core outcome domains included (1) vascular access, (2) fatigue, (3) cardiovascular disease, and (4) mortality 11,143,144 . For each of these core outcome domains, the most critically important outcome measure will be developed following a similar multi-step process including a systematic review, international survey, consensus workshop, pilot and validation study to ensure successful implementation 139,145 . This thesis will describe the process and outcomes of establishing a core outcome measure for vascular access.…”
Section: The Standardised Outcomes In Nephrology Initiativementioning
confidence: 99%
See 1 more Smart Citation